Information flow control in role-based model for distributed objects - Izaki, K.; Tanaka, K.; Takizawa, M. (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
Various kinds of distributed applications are realized in object-based frameworks. Object-based technologies are used to design applications and enhance the interoperability among applications. In addition to realizing the interoperability, the system is required to be secure. The secure system is required to not only protect objects from illegal manipulation but also illegal information flow among objects. We discuss a role-based access control model in the object-based systems and how to resolve illegal information flow in the roles. We define a safe set of roles where no illegal information flow occurs. We discuss an algorithm to check if illegal information flow occurs. In addition, we discuss how to safely perform transactions belonging to unsafe roles.